ASSOCIATIONS EXPOSURE PORNOGRAPHY WITH RISKY SEXUAL BEHAVIOR PREMARITAL ON STREET CHILDREN IN CIMAHI CITY - Rainta Pranitia (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Sexual behavior on street children arose because of great curiosity and encouragement to try new experiences in adolescence with pornographic content that is widespread. Total of street children is growing every year,Â  in 2011 amounted 67.607 children, while total of street children in west java province 2014 amounted 6899 children, and in cimahi city until february 2015 reached 58 children. This study aims to determine the association of pornography exposure with risky sexual behavior pre-marry on street children. This study used analytic survey with cross sectional method, population in this study were all street children located in the Cimahi city on May 26 until June 13, 2015, while sample in this study used total population. Instrument this study in the form of questionnaires. Variable studied in this study is sexual behavior and exposure of pornography. The statistical test used is Chi-Square with CI = 95% Î± = 0.05 (H0 is rejected if p <Î±). The results showed that esposure to pornography has a association with premarital sexual behavior (p value = 0.010) Keywords : sexual behavior, street children, exposure to pornography